Perfect touch - Lowell, Elizabeth, 1944- (William Morrow, an imprint of HarperCollinsPublishers, 2015)
A heart-racing tale in which a former soldier turned rancher and a beautiful designer race to stop a vicious killer--a battle for survival that threatens to explode in an intense and irresistible passion.